Scouting. More than a school of values, a gymnasium of virtues (Journal of Parents and Teachers, 2017)
Scouting brings something different to education in values that children and young people receive in their environment: the possibility of acquiring and developing the strengths that allow them to be good people throughout their lives. And for this their offer is clear, to live unique experiences that little by little require them to live up to the commitment acquired before their peers, throughout the first and significant years of their childhood and youth.
Keywords: education; scouting; values; strengths